Implementasi Model Problem Based Learning Berbantuan Media Pembelajaran Papan Pintar Untuk Meningkatkan Minat Siswa Terhadap Pembelajaran Matematika Di SDN Roto 2 Krucil Probolinggo - ., Andini Nur Firdaussy; ., Fajarotul Khoiroh; ., Putri Oktavia; ., Didit Yulian Krisdiyanto (Jurnal Pendidikan, Sains Dan Teknologi, 2023)
This observation is motivated by the problem of students' lack of interest in mathematics. Most students are unhappy with math because it is difficult to understand and boring to learn. To make it easier for students to understand mathematics, it's a good idea to give an easy example of how to apply math problems using learning media with concrete objects that students like is a good and easy thing. The study of this observational data uses qualitative descriptive analysis that refers to Classroom Action Research (PTK) which is carried out every mathematics learning meeting. The results of this study with the implementation of a problem-based learning model assisted by smart board media can help grade III students of SDN Roto 2, Krucil towards mathematics have increased which initially 70% increased to 90% to increase interest in mathematics learning and be able to think actively and critically in understanding the concept of multiplication..